Wild Edible Plants of Purmandal block of District Samba, J&K (UT), India - Manhas, R.K.; Bhagat, Nisha; Upadhyay, Hina; Gupta, Sanjeev Kumar (Ethnobotany Research and Applications, 2022)
Background: Edible plants that are neither cultivated nor domesticated but can be found in their natural habitat are known as wild edible plants (WEPs). In times of food scarcity, WEPs give a valuable natural nutritional supply as food, diet, and nutrients. Methods: An ethnobotanical field study was conducted in eleven villages of Purmandal using focused group discussions, and interviews through semi-structured questionnaires. Information was gathered from a total of 153 informants (115 females and 38 males). Informants were briefed about the objectives of the study and Prior Informed Consent (PIC) was obtained as per Convention on Biological Diversity (CBD). The various uses of WEPs were quantified as use-reports, and Cultural Importance Value (CI) and Factor informant consensus (Fic) were calculated. Results: Altogether 58 plants belonging to 51 genera and 34 families were used as WEPs. Cucurbitaceae and Rutaceae (5 species each) were the most represented families, and leaves and fruits were the most frequently used plant parts. The contribution of herbs, shrubs, and climbers were 36.2%, 37.9%, and 15.5%, respectively. The maximum CI was recorded for Mangifera indica L., Phyllanthus emblica L., and Bauhinia variegata (L). Benth. The values of Fic varied between 0.95 (medicinal usage) and 0.99 (chutney preparation). Conclusion: Locals of Purmandal have good knowledge of WEPs. Traditional products made from WEPs like Mangifera indica, Phyllanthus emblica and Bauhinia variegata can be commercialized to improve the economic status of the locals. Furthermore, the nutritive values of important species may be studied. Keywords: Wild edible plants, Purmandal, Food security, Sustainable agriculture.